2023
DOI: 10.1126/sciadv.ade2078
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nitrite accumulation at the primary nitrite maximum in the cyclonic eddies in the western North Pacific subtropical gyre

Abstract: Nitrite, an intermediate product of the oxidation of ammonia to nitrate (nitrification), accumulates in upper oceans, forming the primary nitrite maximum (PNM). Nitrite concentrations in the PNM are relatively low in the western North Pacific subtropical gyre (wNPSG), where eddies are frequent and intense. To explain these low nitrite concentrations, we investigated nitrification in cyclonic eddies in the wNPSG. We detected relatively low half-saturation constants (i.e., high substrate affinities) for ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
(101 reference statements)
1
4
0
Order By: Relevance
“…To minimize the potential enhancement of the in-situ rates due to enrichment by tracer concentrations, the final concentrations of 15 N-NH4 + , 15 N-urea and 15 N-NO2were limited to 20 nmol L -1 . The final concentrations of NH4 + , urea and NO2in our incubations were close to or lower than the Ks measured in our study and the reported values for ammonia oxidation, urea oxidation and nitrite oxidation rates measured in the wNPSG and the NWP (Liu et al, 2023;Xu et al, 2019), suggesting an overall substrate limiting condition in our incubations. Therefore, we applied a linear regression approach using equations (1-2), with the following assumptions, to obtain the estimates of the in-situ reaction rates (Wan et al, 2018).…”
Section: Rate Calculationsupporting
confidence: 87%
See 3 more Smart Citations
“…To minimize the potential enhancement of the in-situ rates due to enrichment by tracer concentrations, the final concentrations of 15 N-NH4 + , 15 N-urea and 15 N-NO2were limited to 20 nmol L -1 . The final concentrations of NH4 + , urea and NO2in our incubations were close to or lower than the Ks measured in our study and the reported values for ammonia oxidation, urea oxidation and nitrite oxidation rates measured in the wNPSG and the NWP (Liu et al, 2023;Xu et al, 2019), suggesting an overall substrate limiting condition in our incubations. Therefore, we applied a linear regression approach using equations (1-2), with the following assumptions, to obtain the estimates of the in-situ reaction rates (Wan et al, 2018).…”
Section: Rate Calculationsupporting
confidence: 87%
“…For depths that exhibited typical M-M type kinetic response, the Ks of ammonia oxidation and nitrite oxidation varied between 24-390 nmol L -1 , and 61-225 nmol L -1 , falling in the range of reported Ks in the open ocean systems (e.g., Liu et al, 2023;Mdutyana et al, 2022;Wan et al, 2018). For urea oxidation, the Ks varied in the range 97-263 nmol N L -1 , which was higher than the Ks for NH4 + at the corresponding depths, suggesting a higher affinity towards NH4 + in marine AOA.…”
Section: Kinetic Traits Determine Marine Nh4 + Urea and No2distributionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our results indicated that the growth rates of AO could approach those of pure cultures growing under NH 4 + ‐replete conditions and in the absence of grazing control. However, a recent study has shown that the half‐saturation constants of NH 4 + oxidation in the deep euphotic zone of the North Pacific can be no more than 10 nmol L −1 (Liu et al., 2023). The implication is that even ambient NH 4 + concentrations may be near saturated concentrations.…”
Section: Discussionmentioning
confidence: 99%